2005
DOI: 10.1016/j.cub.2005.08.061
|View full text |Cite
|
Sign up to set email alerts
|

The Aspergillus nidulans Phytochrome FphA Represses Sexual Development in Red Light

Abstract: Phytochrome photoreceptors sense red and far-red light through photointerconversion between two stable conformations, a process mediated by a linear tetrapyrrole chromophore. Originally, phytochromes were thought to be confined to photosynthetic organisms including cyanobacteria, but they have been recently discovered in heterotrophic bacteria and fungi, where little is known about their functions. It was shown previously in the ascomycetous fungus Aspergillus nidulans that asexual sporulation is stimulated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
332
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 329 publications
(344 citation statements)
references
References 22 publications
6
332
0
6
Order By: Relevance
“…7) FphA (Fungal phytochrome A) has been identified as a red light receptor in A. nidulans. 8) These successful studies of photoreaction in other filamentous fungi support the speculation that A. oryzae can also perceive various types of light with photoreceptors and show responses via light signal transduction pathways. Indeed, recent genome sequencing of A. oryzae indicates the existence of homologs of certain light-related genes in other filamentous fungi (Table 1).…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…7) FphA (Fungal phytochrome A) has been identified as a red light receptor in A. nidulans. 8) These successful studies of photoreaction in other filamentous fungi support the speculation that A. oryzae can also perceive various types of light with photoreceptors and show responses via light signal transduction pathways. Indeed, recent genome sequencing of A. oryzae indicates the existence of homologs of certain light-related genes in other filamentous fungi (Table 1).…”
mentioning
confidence: 65%
“…6) Recently, in A. nidulans, a fungal phytochrome, FphA, was identified as a red light receptor that putatively binds to biliverdin chromophores. 8) In Aspergillis spp., it has been found that development is affected by light. A. flavus, A. parasiticus, and A. nidulans grown under light produce 5-to 10-fold more conidia than those grown under dark.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This development is repressed by light, aeration, and in submerged culture, whereas it is promoted by the presence of a medium/air interface and the absence of light. To date, the fungal phytochrome FphA is the only analyzed developmental photosensor of A. nidulans (Blumenstein et al, 2005;Purschwitz et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This development is repressed by light, aeration, and in submerged culture, whereas it is promoted by the presence of a medium/air interface and the absence of light. To date, the fungal phytochrome FphA is the only analyzed developmental photosensor of A. nidulans (Blumenstein et al, 2005;Purschwitz et al, 2006).Inspection of the genome of the homothallic ascomycete A. nidulans (Galagan et al, 2005) revealed only a single putative CRY/photolyase-like gene, here termed cryA. The deduced protein of 567 amino acids includes a PHR domain that contains both DNA photolyase and FAD-binding domains.…”
mentioning
confidence: 99%